Banks and economic growth in developing countries: What about Islamic banks? - Saida Daly; Mohamed Frikha (Cogent Economics & Finance, 2016)
Islamic banks (IBs) have a significant role in the growth of gross domestic product of the developing countries. The Islamic participatory schemes integrate the assets of lenders and borrowers. They allow enable IBs to lend on a longer term basis to create projects with higher risk-return profiles and, thus, to support economic growth. Our investigation examines the ontribution of Islamic finance in economic growth. Using a panel data-set, we compare between IBs and conventional banks in their adding to economic growth. We studied a sample of 120 banks between 2005 and 2012. By means of three ordinary least-square regressions, our empirical investigation reveals that the development of non-usurious banks supports economic growth. Moreover, the cooperation between the two financing modes improves economic growth. The integration of this new funding never neglected the role of the conventional method of financing. The practice of IBs is also away from their theoretical mode in terms of participation results.
Keywords: 330; Islamic banks; conventional banks; economic growth; ordinary least square